Analysis of Livin' By Mandiri Application Quality With Iso 25010 Method - Pratama, Bagas (Universitas Negeri Padang, 2023)
In the increasingly advanced digital era, mobile applications have become one of the important tools in providing banking services to customers. The Livin' by Mandiri application is one of the mobile banking applications that Bank Mandiri offers its customers. This study aims to analyze the quality of the Livin' by Mandiri application. This research uses the ISO 25010 method. Data collection techniques in this study were carried out by observation and literature study. The data obtained was then systematically analyzed in accordance with the ISO 25010 framework. The results showed that the Livin' by Mandiri application has a high level of functional suitability, is reliable and stable, fast and responsive, easy to use and navigate, well maintained and portable and can be used on various devices, including smartphones, tablets and laptops.